Wounding Therapies for Prevention of Photocarcinogenesis - Frommeyer, Timothy C.; Rohan, Craig A.; Spandau, Dan F.; Kemp, Michael G.; Wanner, Molly A.; Tanzi, Elizabeth; Travers, Jeffrey B. (Frontiers in Oncology, 2022)
The occurrence of non-melanoma skin cancer (NMSC) is closely linked with advanced age and ultraviolet-B (UVB) exposure. More specifically, the development of NMSC is largely due to diminished insulin-like growth factor-1 (IGF-1) signaling from senescent dermal fibroblasts in geriatric skin. Consequently, keratinocyte IGF-1 receptor (IGF-1R) remains inactive, resulting in failure to induce appropriate protective responses including DNA repair and cell cycle checkpoint signaling. This allows UVB-induced DNA damage to proliferate unchecked, which increases the likelihood of malignant transformation. NMSC is estimated to occur in 3.3 million individuals annually. The rising incidence results in increased morbidity and significant healthcare costs, which necessitate identification of effective treatment modalities. In this review, we highlight the pathogenesis of NMSC and discuss the potential of novel preventative therapies. In particular, wounding therapies such as dermabrasion, microneedling, chemical peeling, and fractionated laser resurfacing have been shown to restore IGF-1/IGF-1R signaling in geriatric skin and suppress the propagation of UVB-damaged keratinocytes. This wounding response effectively rejuvenates geriatric skin and decreases the incidence of age-associated NMSC.